[Imported malaria in Tunisia: consequences on the risk of resurgence of the disease]. - (:unkn) unknown (My University, 2010)
Although malaria has been eradicated in Tunisia since 1979, the disease is still a health issue due to the persistence of mosquitoes and coexistence with a potential parasite reservoir in the form of imported cases. From 1999 to 2006, 98 cases of imported malaria were diagnosed at the Pasteur Institute in Tunis where nearly 30% of national cases are recorded. Tunisians accounted for 24.5% of these cases versus 75.5% involving foreigners. The occurrence rate has steadily increased in volunteer workers, businessmen, diplomats and athletes who together accounted for 41.7% of cases in 1995 as compared to only 17.4% in 1980 (p<0.01). Most cases (96.5%) were imported from sub-Saharan Africa. The most frequent countries involved in importation were Cote d'Ivoire (23 cases) and Mali (8 cases) that are now linked to Tunisia by regular flights. About one third of patients were asymptomatic at the time of diagnosis. This finding underlines the importance of recommending systematic screening in high-risk groups. Fever (70.6%) and gastro-intestinal manifestations (27.9%) were the most frequent clinical findings in the 69 symptomatic cases. Plasmodium falciparum (71.4%) was the most common species followed by Plasmodium ovale (19.4%). Gametocytes were detected in 9.2% of subjects, thus creating a theoretical source of infection for mosquitoes especially since 60.2% of all cases were recorded between June and October when mosquitoes are active in Tunisia. Due to increasing exchange with endemic malaria areas in Africa that has resulted in a higher incidence of imported cases and a futher risk of introduction of tropical mosquito species as well as to global warming that promotes plasmodium transmission, greater vigilance is necessary to ensure eradication of malaria in Tunisia.
Keywords: African Research